Language Gap in Reach of "The Real Cost": Examination of a Federal Mass Media Campaign From 2017 to 2019. Issue 9 (29th March 2021) - Mantey, Dale S; Clendennen, Stephanie L; Ruiz, Felisa A; Perry, Cheryl L
Abstract: Introduction: Approximately 25% of youth in the United States speak a language other than English at home. These youth may have less exposure to English-speaking media, including public smoking prevention initiatives such as the FDA's "The Real Cost" campaign. Research is needed to explore potential gaps in the reach of "The Real Cost" campaign among bilingual youth. Aims and Methods: Data were pooled from the 2017–2019 National Youth Tobacco Surveys. Participants were n = 12 803 middle and high school students who were either: (1) susceptible never smokers; or (2) ever smokers that had smoked less than 100 cigarettes; these criteria reflect the FDA's definition of "target population" for "The Real Cost" campaign. Multiple, logistic regression analyses examined the relationship between speaking a language other than English at home (ie, bilingual) and self-reported exposure to "The Real Cost" campaign among both samples. Analyses controlled for sex, race/ethnicity, grade level, tobacco marketing exposure, and current tobacco use. Results: The majority (61.7%) of youth who met "target population" criteria self-reported exposure to "The Real Cost" from 2017 to 2019. Regression analyses found that youth who reported speaking a language other than English at home were significantly less likely to self-report exposure to "The Real Cost" campaign (adjusted odds ratio: 0.85; p < .001), adjusting for covariates. Conclusions: Bilingual youth were significantly less likely to report exposure to "The Real Cost" campaign. Findings suggest the need to develop methods of increasing reach among bilingual youth, given the high smoking prevalence among these youth. Implications: This study highlights a social and cultural gap in the reach of the FDA's "The Real Cost" campaign. Agencies such as FDA should consider enhancing existing mass media campaigns to reach diverse communities, including the nearly 25% of youth who speak a language other than English.